Exploring the Role of Landscape Architecture in Advancing Environ mental Equity and Climate Justice (Prakriti - The International Multidisciplinary Research Journal, 2025)
Landscape Architects through their expertise and knowledge can shape human experiences by adopting equitable design strategies into designing healthy, equitable and inclusive open spaces and balancing the scale of environmental justice. People with different physical abilities and belonging to different economic, social and ethnic origins tend to dwell within the cities. Public parks and open spaces are a perfect aid for this rapidly growing socio-economic discrepancy in any urban setting. Hence inclusive and accessible landscape designs reflect and celebrate the social diversity and identity of the users by recognising different cultures, values, histories and aspirations of the people within the communities. Through intensive studies, researchers have observed that public spaces also contribute to the upliftment of both physical and psychological well being within urban areas. In countries of Global South where urbanization is occurring at a tremendous pace, safeguarding and promoting these natural ecologies should take place simultaneously along with social and economic development. These countries are designing landscapes that are related to existing green-blue infrastructure and forming adaptive spaces within landscapes that provide resilience to the cities during times of disaster. Thus, creating landscapes that serve as the connection between the city and nature through their ecologies should be implemented and designed for the proper functioning of cities. Understanding and implementation of landscape architecture strategies in current global times is crucial in synthesising the existing ecological systems, social practices and values and also to promote social and environmental equity. The paper will analyse the role and importance of landscape architecture in current scenario and its function in creating spaces that overall helps in providing and improving resilience in urban areas. The paper will also investigate the factors and possibilities of successful implementation of landscape architecture solutions in cities to achieve environmental justice and how communities perceive these landscapes within those urban areas
Keywords: urban studies; landscape; environmental equity; climate justice; public spaces.